Evaluation of WO2011045166A1, Fkbp52–tau interaction as a novel therapeutical target for treating the neurological disorders involving tau dysfunction. (July 2015) - Zheng, Feng; Zhang, Biao; Sun, Yanan; Qiu, Mingfeng; Su, Jing
<x xml:space="preserve">Abstract</x> Introduction: This invention provides the screening methods of candidate compounds, the diagnostic methods and the methods of treatment of human cognitive diseases, and also gives out several potential candidate compounds. The invention establishes that the FKBP52–Tau interaction provides a new target that may be used advantageously for novel therapeutic approaches for neurological disorders involving Tau dysfunction, and especially for Alzheimer's disease. Areas covered: The invention generally relates to neuroprotection and repair in neurological disorders involving Tau dysfunction (including Alzheimer's disease). The invention describes a direct interaction between FKBP52 and Tau, the screening methods for molecules acting on the FKBP52–Tau interaction, in order to modulate the detrimental effect of pathogenic Tau. Finally, it discusses therapeutic, diagnostic, prognostic and monitoring assays of neurological disorders involving Tau dysfunction. Expert Opinion: Several methods or techniques were used to determine the validity of screening methods, involving biochemistry, immunology, fluorescence analysis and cell experiment. Candidate compounds mentioned in the patent include FK506 derivatives, rapamycin derivatives and pipecolyl-α-keto-amid compounds. However, the mechanism, the structural similarity and the biological activity were unmentioned, which may partly reduce the practicability of the invention. The FKBP52–Tau interaction as a novel target for neurodegenerative diseases is promising. FKBP52 is capable of preventing polymerization of tubulin and maintaining axonal transport. In AD patients' brain, the high level of Tau protein phosphorylation is directly related to the decrease of FKBP52. The FKBP52–Tau interaction may provide a new critical path for treatment of neurodegenerative diseases, and new molecules will possess higher affinity and efficiency.